Clinical characteristics and prognostic factors of ovarian granulosa cell tumors: a retrospective cohort study - Fan, Yinbai; Zeng, Yanzhen (Frontiers in Oncology, 2026)
BackgroundOvarian granulosa cell tumors (OGCTs) are rare sex cord-stromal tumors comprising distinct histopathological entities: adult-type and juvenile-type GCTs. Comparative data on clinical characteristics and outcomes between these subtypes remain limited.MethodsA retrospective analysis was performed on 29 patients diagnosed with OGCTs (26 adult-type and 3 juvenile-type) from January 2008 to December 2024. Clinical data, tumor markers, pathological features, surgical approaches, and survival outcomes were assessed. Relapse-free survival (RFS) was evaluated using Kaplan-Meier analysis. Given the small juvenile cohort (n=3) with zero recurrence events during follow-up and distinct biological characteristics, prognostic factor analysis using Cox regression was restricted to adult-type GCTs (n=26, 3 recurrence events).ResultsOGCTs exhibited distinct age-related patterns, with adult-type tumors primarily affecting postmenopausal women (median age 50.5 years) and juvenile-type tumors occurring in pediatric patients (median age 13.0 years) (p = 0.005). Most patients (89.7%) presented with FIGO stage I disease, with stage IC being the most common (55.2%). Abdominal mass was the most frequent presenting symptom (51.7%). Immunohistochemically, both subtypes showed high positivity for inhibin-α (93.1%), calretinin (92.3%), and CD99 (95.0%). Fertility-sparing surgery was performed in all juvenile-type cases (100%) compared to 19.2% of adult-type cases (p = 0.018). Recurrence occurred in three patients (10.3%), all of whom had adult-type tumors. In adult-type GCTs, advanced FIGO stage (IC-III) was the only independent prognostic factor for RFS in multivariate analysis (HR 13.57, 95% CI 1.19-154.3, P = 0.035). Preoperative CA125 showed a trend (HR 1.04 per U/mL, P = 0.079) that did not reach statistical significance.ConclusionsWithin the constraints of limited follow-up (median 60 months) and small sample size, early-stage OGCTs demonstrate favorable short- to intermediate-term outcomes, with FIGO stage as the primary prognostic determinant in adult-type disease. Fertility-sparing surgery appears feasible in early-stage disease, particularly for juvenile-type tumors. However, the short follow-up duration likely underestimates true long-term recurrence rates in adult-type GCTs, which characteristically recur late.LimitationsSmall sample size (particularly juvenile cohort, n=3), single-center design, relatively short follow-up (median 60 months; 72% <8 years), and absence of GCT-specific tumor markers (Inhibin B, AMH) limit generalizability and assessment of long-term outcomes.